Usage of Mobile Applications at Night and its Association with Sleep Pattern and Academic Performance of the Medical Students of UniKL-RCMP, Ipoh, Malaysia - ATM Emdadul Haque (Journal of Global Pharma Technology, 2017)
Background: Smartphone has become a mainstream medium, in the healthcare setting because of quick access to medical information, enhance students’ learning in a clinical environment and increases knowledge score. Therefore, this research was performed to determine if there was an association of the mobile applications usage at night on sleep pattern and academic performance of the medical students of UniKL RCMP. Aim: This study was done to determine the relationship between socio-demographic factors with 3 elements, which are mobile application usage, sleep quality and quantity and academic performance. Methods: This cross-sectional study involved Year-2 till Year-5 medical students of UniKL RCMP. The sample size was calculated to be 214 students with 95% confident level, by using Opine application. The study was conducted from December 2016 to January 2017. The quota sampling method was used. A set of questionnaires were developed and computed as the variables of this study. Statistical analysis was done in SPSS 21 using appropriate statistical test, p<0.05 was considered as significant. Results:  Out of 300 only 215 questionnaires were returned.  100% of the current study respondents use a smartphone. There was a correlation between average total time smartphone apps used before sleep at night and feeling tired after waking up in the morning. This study result showed that usage of smartphone apps during class could lead to losing of attention. Conclusions: There were a correlation between mobile apps usage at night on sleep pattern. The heavier the usage of smartphone apps, the more sleep quantity and quality goes down. Though, students’ academic performance was not significantly associated with the use of mobile apps.